A novel TUBG1 mutation with neurodevelopmental disorder caused by malformations of cortical development. (26th February 2021) - Shen, Ru; Zhang, Zhen; Zhuang, Yu; Yang, Xiaohong; Duan, Lifen
Abstract : Neurodevelopmental disorder caused by malformations of cortical development is a rare neurological disease. Heterozygous missense variants in the TUBG1 gene lead to malformations of human cortical development, which further result in intellectual disability, developmental retardation, and epilepsy. To the best of our knowledge, only thirteen patients and a total of nine pathogenic TUBG1 variants have been described in the published literature. This study reports the case details and genetic data analysis of a girl (aged 8 years, 9 months) with developmental delay, psychomotor regression, epilepsy, and left external ear deformity. A novel TUBG1 mutation was identified by whole-exome sequencing and Sanger sequencing, confirming that this mutation may be the cause of the neurodevelopmental disorders. This case report characterizes the phenotypic spectrum, molecular genetic findings, and functional consequences of novel pathogenic TUBG1 variants in neurodevelopmental disorders caused by cortical development malformations.